PENENTUAN HARGA KONTRAK ASURANSI JIWA DWIGUNA UNIT LINK MENGGUNAKAN METODE POINT TO POINT - Dwi Susanti; Iin Irianingsih; Qurrotun A’yun A; Muhamad Deni Johansyah; Badrulfalah Badrulfalah (LPPM UNIBI, 2019)
Some people now prefer to invest their money because it is considered more profitable than following traditional life insurance. Life insurance that there is an element of investment and provide protection to the insured is endowment unit link life insurance. Endowment unit link life insurance is an insurance that combines traditional endowment insurance with modern unit link insurance. In this research, the formulation of single premium net life of endowment unit link life insurance using Point to Point method to find the value of premium to be paid by the insured to the insurance company. Data used in this research is stock closing price for case study at PT. Bank Central Asia Tbk and the 45 years old insured data obtained from Mortalita Indonesia Table 2011. Based on the research result, the single premium net endowment unit link life insurance of 10 years for a man aged 45 years with the initial stock price of Rp 15,500 and the number of shares of 100 shares is Rp 15,605,951.